2010
DOI: 10.3947/ic.2010.42.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-ResistantEnterococcus faeciumMeningitis Treated with Linezolid: A Case Report and Review of the Literature

Abstract: Vancomycin-resistant enterococci (VRE) infection is a serious problem because optimal therapy has not been established. Different agents in various combinations, including teicoplanin, chloramphenicol, and quinupristin/dalfopristin, have been used to treat patients with VRE meningitis, but the efficacy of these agents is not satisfactory because of their limited ability to penetrate into the cerebrospinal fluid.We report a case of nosocomial vancomycin-resistant Enterococcus faecium meningitis in a patient wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Among 19 identified cases involving linezolid for the treatment of CNS infections caused by VRE faecium , 15 reported clinical cure (78.9%), of which monotherapy with linezolid was used in 53.3% (8/15) of cases (Table 1). 7-9,12,14,19-21 The remaining 7 cases describe clinical success while concurrently receiving 1 of the following: ampicillin, 13 gentamicin, 10 rifampin, 20 quinupristin/dalfopristin, 11 and daptomycin. 15,17 Entenza et al 39 reported in vitro synergistic killing against MDR (ampicillin, vancomycin, high-level aminoglycoside resistant) Enterococcus strains when linezolid was combined with daptomycin.…”
Section: Reported Cases Of Vre Faecium Cns Infections Treated With LImentioning
confidence: 99%
See 2 more Smart Citations
“…Among 19 identified cases involving linezolid for the treatment of CNS infections caused by VRE faecium , 15 reported clinical cure (78.9%), of which monotherapy with linezolid was used in 53.3% (8/15) of cases (Table 1). 7-9,12,14,19-21 The remaining 7 cases describe clinical success while concurrently receiving 1 of the following: ampicillin, 13 gentamicin, 10 rifampin, 20 quinupristin/dalfopristin, 11 and daptomycin. 15,17 Entenza et al 39 reported in vitro synergistic killing against MDR (ampicillin, vancomycin, high-level aminoglycoside resistant) Enterococcus strains when linezolid was combined with daptomycin.…”
Section: Reported Cases Of Vre Faecium Cns Infections Treated With LImentioning
confidence: 99%
“…6 Furthermore, anecdotal evidence currently guiding treatment selection is limited to observational case reports and case series. 3,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Daptomycin and linezolid have found a place in therapy for VRE bloodstream infections; however, consensus on which agent is optimal for treating VRE faecium CNS infections remains to be determined. 23 Cases of VRE faecium meningitis sourced from the blood are challenging to treat with these agents because daptomycin offers limited penetrability into the CSF, and linezolid, for Enterococcus species, provides bacteriostatic activity.…”
Section: Central Nervous System (Cns) Infections Caused Bymentioning
confidence: 99%
See 1 more Smart Citation